Left and Right in MPLA’s Angolan Socialism - Fragoso, Nuno (História: Questões & Debates, 2025)
Although the epithet of Socialist attributed to Agostinho Neto’s presidency at the MPLA, dates to the anti-colonial struggle, the official adherence was delayed until October 1976, a year after independence. Far from a voluntary option by the leadership, least of its president, it is here argued that it was the result of a specific context combining unbearable domestic and international pressures on Neto and his loyalists - left and right wings. A stronger-than-ever threat to Neto’s leadership, through Nito Alves’s attempted coup in May 1977, articulated with the USSR’s decisive push for a clear standing and the desperate need for Cuba military support, did not leave much option. Nonetheless, as demonstrated here, Neto and the right-wing ingeniously found a way-out, cocooning a right-wing praxis with a left-wing discourse, founding the MPLA’s façade Socialism. This paper analysis such dynamics through Agostinho Neto’s administration, articulating the domestic and international contexts.